THE DEVELOPMENT OF ELECTRONIC TOPIC MODULE WITH INTEGRATED 2D SIMULATION AND AUGMENTED REALITY APPLICATION: MODULE VALIDITY - Mohd Hamizan Jafini; Irdayanti Mat Nashir; Ahmad Zulhairie Abu Bakar; Nurhan Ayub; Yusmahnizam Yusof (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The evolution of education has significantly transformed Teaching and Learning (T&L) sessions through the integration of technologies and digital tools, offering students new learning opportunities. This shift has led to changes in Malaysia’s educational curriculum, particularly in technical and vocational subjects. Design and Technology (D&T), a new subject introduced to replace Integrated Life Skills. Research shows that the electronics topic in D&T is particularly challenging, making it difficult for students to achieve their highest mastery levels as outlined in the Curriculum Standard and Assessment Documentation (DSKP). Both teachers and students often struggle with completing electronic projects due to limited technical skills and students’ poor visualization abilities. This study aims to validate the module validity in electronic topic module. The research adopts a quantitative research design with Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model approach, emphasizing the implementation phase. The module validity will be evaluated by nine experts in D&T and Technical and Vocational field. The study of the data will be analyzed by using the Content Validity Index (CVI). The results show that some items have a minimum CVI value of 0.78, and the S-CVI value is also 0.983, indicating the module validity is valid and acceptable. This demonstrates that the module is ready for pilot and actual studies to assess its usability and effectiveness. In conclusion, the module has been validated by experts, improving its quality and helping to identify areas for future research, particularly in evaluating its usability and effectiveness.